2020
DOI: 10.1177/2472555220915851
|View full text |Cite
|
Sign up to set email alerts
|

A Whole Genome-Wide Arrayed CRISPR Screen in Primary Organ Fibroblasts to Identify Regulators of Kidney Fibrosis

Abstract: Kidney fibrosis presents a hallmark of chronic kidney disease. With ever-increasing patient numbers and limited treatment options available, novel strategies for therapeutic intervention in kidney disease are warranted. Fibrosis commonly results from a wound healing response to repeated or chronic tissue damage, irrespective of the underlying etiology, and can occur in virtually any solid organ or tissue. In order to identify targets relevant for kidney fibrosis, we aimed to employ CRISPR screening in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The authors identified the majority of kinase genes with known regulatory roles in TNF-α-mediated NF-κB signaling at a higher success rate than observed with previous RNAi-based studies. As with the work from Turner et al, 5 these data demonstrate that lentiviral-based arrayed screening reagents can be supplied at scale and with sufficient consistency to obtain meaningful screening results.…”
Section: Screening Libraries and Technologiessupporting
confidence: 63%
See 1 more Smart Citation
“…The authors identified the majority of kinase genes with known regulatory roles in TNF-α-mediated NF-κB signaling at a higher success rate than observed with previous RNAi-based studies. As with the work from Turner et al, 5 these data demonstrate that lentiviral-based arrayed screening reagents can be supplied at scale and with sufficient consistency to obtain meaningful screening results.…”
Section: Screening Libraries and Technologiessupporting
confidence: 63%
“…Turner et al 5 describe the development of a high-content assay to study kidney fibrosis using primary human kidney fibroblasts. To identify novel targets that can modulate kidney fibrosis, the authors performed genome-wide arrayed genetic screening using lentiviral gRNA libraries.…”
Section: Translatable Modelsmentioning
confidence: 99%
“…However, there are many different forms of collagen and assays and reagents to specifically and quantitatively assess whether mature collagen is sparse. Interestingly, several recent screening approaches utilize immunofluorescence of both α-SMA and collagen, which could be seen as the first step to a multiparametric approach (Weigle et al, 2019;Turner et al, 2020). Schimmel et al (2020) analyzed three readouts, namely, the proliferation of human CFs, modulation of apoptosis, and expression of ECM, when screening a natural compound library for molecules for the treatment of cardiac fibrosis.…”
Section: Readouts Of Cardiac Fibrosis Assaysmentioning
confidence: 99%
“…However, there are many different forms of collagen and assays and reagents to specifically and quantitatively assess whether mature collagen is sparse. Interestingly, several recent screening approaches utilize immunofluorescence of both α-SMA and collagen, which could be seen as the first step to a multiparametric approach ( Weigle et al, 2019 ; Turner et al, 2020 ).…”
Section: In Vitro Assays For Cardiac Fibrosismentioning
confidence: 99%
See 1 more Smart Citation